To find the 62nd term of an arithmetic sequence, we can use the formula:
\[ a_n = a_1 + (n-1)d \]
where:
- \( a_n \) is the nth term of the sequence
- \( a_1 \) is the first term of the sequence
- \( d \) is the common difference between terms
- \( n \) is the position of the term we want to find
In this case, the first term (\( a_1 \)) is -27, the common difference (\( d \)) is 6 (21 - (-27) = 6), and we want to find the 62nd term (\( n = 62 \)).
Plugging these values into the formula, we get:
\[ a_{62} = -27 + (62-1)6 \]
\[ a_{62} = -27 + 61*6 \]
\[ a_{62} = -27 + 366 \]
\[ a_{62} = 339 \]
Therefore, the 62nd term of the sequence is 339.
Find the 62nd term of the arithmetic sequence -27-21,-15
1 answer